2018
DOI: 10.1016/j.tplants.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Out of Shape During Stress: A Key Role for Auxin

Abstract: In most abiotic stress conditions, including salinity and water deficit, the developmental plasticity of the plant root is regulated by the phytohormone auxin. Changes in auxin concentration are often attributed to changes in shoot-derived long-distance auxin flow. However, recent evidence suggests important contributions by short-distance auxin transport from local storage and local auxin biosynthesis, conjugation, and oxidation during abiotic stress. We discuss here current knowledge on long-distance auxin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(146 citation statements)
references
References 73 publications
(113 reference statements)
2
143
1
Order By: Relevance
“…From an agricultural perspective, a number of Arabidopsis FMOs have been specifically expressed in other crop plants with an aim to improve stress performance and to identify analogous functionality. The field has predominantly focused on the exploitation of YUCCAs, based on their physiological role in hormone production, an improved abiotic stress response [110] and the overall need for crop resilience under future adverse climatic conditions [111]. Indeed, when AtYUC6 was stably transformed into important crop plants such as potato (Solanum tuberosum), sweet potato (Ipomoea batatas), soybean (Glycine max), and poplar (Populus alba × P. glandulosa), improved abiotic resistance was observed in all cases [112][113][114][115].…”
Section: The Unexploited Potential Of Plant Fmos For Agriculture and mentioning
confidence: 99%
“…From an agricultural perspective, a number of Arabidopsis FMOs have been specifically expressed in other crop plants with an aim to improve stress performance and to identify analogous functionality. The field has predominantly focused on the exploitation of YUCCAs, based on their physiological role in hormone production, an improved abiotic stress response [110] and the overall need for crop resilience under future adverse climatic conditions [111]. Indeed, when AtYUC6 was stably transformed into important crop plants such as potato (Solanum tuberosum), sweet potato (Ipomoea batatas), soybean (Glycine max), and poplar (Populus alba × P. glandulosa), improved abiotic resistance was observed in all cases [112][113][114][115].…”
Section: The Unexploited Potential Of Plant Fmos For Agriculture and mentioning
confidence: 99%
“…In addition to auxin transport, local auxin metabolism also influences the root-tip auxin distribution and the resulting root phenotypes, and can be regulated by other hormones and environmental conditions (Ljung, 2013;Korver et al, 2018). Key auxin synthesis and conversion enzymes have been shown to be cell type specific (Stepanova et al, 2008;Xuan et al, 2015) and influence auxin patterning (Brumos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that MYC2 mediates JA-induced inhibition of apical root growth by directly suppressing the expression of auxin-responsive PLTs. This also suggested that auxin and its downstream regulators mediate the stress-induced inhibition of root growth, and the hypothesis is supported by an increasing number of studies [52][53][54].…”
Section: Auxin and Root Developmentmentioning
confidence: 77%